PENGARUH MODEL PEMBELAJARAN REALISTIC MATHEMATIC EDUCATION BERBASIS ALAT PERAGA TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI KELAS II UPT SPF SDN 10182 PANCUR BATU - Ambarita, Gabrielli; Patri Janson Silaban; Irmina Pinem; Juliana; Jhonas Dongoran (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Realistic Mathematics Education learning model based on teaching aids on student learning outcomes in Mathematics subjects in class II UPT SPF SDN 101822 Pancur Batu Learning Year 2024/2025. The research method used was One Group Pretest-Posttest Design. The research subjects were all class II students totaling 28 people. The results showed an increase in the average score from the pretest of 48.58 to 76.78 in the posttest. A total of 24 out of 28 students (86%) achieved learning completeness after the application of the Realistic Mathematics Education learning model based on teaching aids. Statistical analysis shows the rcount value of 0.932 which indicates a very strong correlation between the application of the learning model and learning outcomes. The t-test shows that the t-count of 13,112 is greater than the t-table of 2.056, from the results of the t-test there is a significant influence between the use of the Realistic Mathematics Education learning model on student learning outcomes. And also the Realistic Mathematics Education learning model based on props effectively improves student learning outcomes in the material of multiplication counting operations. This model makes it easier for students to understand concepts concretely and meaningfully, and increases interest, motivation, and active participation in the learning process.